Tradycje winiarskie w literaturze lubuskiej w kontekście regionalnej polityki miejsca = Wine traditions in literature of Lubusz land in the context of the regional policy of place - Gieba, Kamila (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the motif of wine in postwar literature about Lububsz Land and the regional politics of place and the politics of memory. The politics concenrs three aspects of local imaginary geography: arcadia, Piast`s myth, and multicultiralism of borderlines. The research materials are selected poetry, fairy tales and novels about the Lubusz Land.
Keywords: wino; Ziemia Lubuska; polityka miejsca; region; wine; Lubusz Land; politics of place